Social Community Participation in Household Waste Management - Mohammad Djaelani (metromedia.education, 2021)
The increase in population in the city has an impact on the waste produced. Especially with household waste. In addition, the varied consumption patterns of urban communities have the impact of causing waste that will disrupt the quality of life of the community. Therefore, it is necessary to carry out waste management. Waste management is carried out in 5 stages. These stages are 1) Waste collection; 2) Garbage collection; 3) Waste removal; 4) Garbage transportation; 5) Waste processing. The research focus that is the center of attention is waste management from planning to final waste disposal which includes aspects of operational techniques. The type of research used in this study is a type of qualitative research with an exploratory research design. the results of research that has been carried out by the community have known how to process waste in a simple way. However, its application in everyday situations is still rarely done. There are still many people who do not differentiate between organic and inorganic waste. But now urban communities are no longer burning their household waste. The waste from each household has been transported to a final disposal site or final processing place at an independent cost.